Quantum diffusion in liquid para-hydrogen from ring-polymer molecular dynamics. - Miller, T; Manolopoulos, D (2005)
We have used the ring-polymer molecular dynamics method to calculate approximate Kubo-transformed velocity autocorrelation functions and self-diffusion coefficients for low-pressure liquid para-hydrogen at temperatures of 25 and 14 K. The resulting diffusion coefficients are shown to be consistent with experimental shear viscosities and the established finite-size relation D(L) approximately = D(infinity)-2.837k(B)T6pietaL, where k(B) is the Boltzmann constant, T the absolute temperature, eta the shear viscosity, and L the length of the (cubic) simulation cell. The diffusion coefficients D(L) obtained in simulations with finite system sizes are therefore too small. However, the extrapolation to infinite system size corrects this deficiency and leads to excellent agreement with experimental results. This both demonstrates the influence of system-size effects on quantum mechanical diffusion coefficients and provides further evidence that ring-polymer molecular dynamics is an accurate as well as practical way of including quantum effects in condensed phase molecular dynamics.